(untitled) (Journal of Medical & Health Sciences Review, 2025)
Context: Palliative care is specialized medical care focused on improving the quality of life of patients with serious illnesses through symptom management and holistic support. To care for patients with advanced and incurable illnesses, medical students must have the necessary knowledge, skills, and attitudes. Objective: This study aims to assess undergraduate medical students’ knowledge, attitudes, and influencing factors regarding palliative care. Understanding these factors is crucial for addressing gaps in education and ensuring that future healthcare needs are met effectively. Methods: This descriptive cross-sectional study was conducted with medical students at Ayub Medical College, Abbottabad, from September 2023 to March 2024. The data were collected via a validated physical questionnaire via a nonprobability convenience sampling technique. A total of 242 samples were calculated via the WHO sample size calculation tool. Ethical approval was obtained from the Institutional Ethical Review Committee of Ayub Medical Institute. The data were analyzed via SPSS version 26. Results: We conducted this study with 242 medical students (142 males, 100 females; mean age 21.68 ± 1.71 years). The majority were unmarried, hostelites, and pursuing MBBS degrees. The results revealed that 45% of the participants had knowledge of palliative care, whereas 55% did not. Conclusion: This study highlights the need to integrate palliative care into medical curricula and provide hands-on experience to senior medical students to increase their confidence in its delivery, as more than half of the students lack knowledge about palliative care.